The effects of photoperiod on the growth, protein amount and pigment content of Chlorella vulgaris - Kendırlıoglu, G.; Agırman, N.; Cetın, A. K. (Fırat University, 2015)
The well-known correlation between algae and renewable energy sources and in this fact has brought about a great interest for seeking growth conditions of algae. Light is the one of the most important factor for growth and contents of algae. In this study, the effect of different light regimes on the growth rate, chlorophyll and protein amounts were determined. And the results were indicated significant varieties in culture at different light/dark period. The maximum growth rate was 16/8 h light/dark period. Also, when we have investigated chlorophyll and protein contents, we obtained remarkable diversity under different regimes. These observations suggest that the maximum chlorophyll and protein amounts (235, 53; 386, 5 µg/mL) were 20/4 h periods

Algler ve yenilenebilir enerji kaynakları arasındaki ilişki, alglerin büyüme şartlarının araştırılmasının ana nedenini oluşturmaktadır. Işık, alglerin gelişim ve içeriğine etki eden en önemli faktörlerden birisidir. Bu çalışmada, farklı ışık rejimlerinin Chlorella vulgaris’in büyüme oranı, protein ve klorofil miktarına olan etkisi incelenmiştir. Araştırmadan elde edilen sonuçlar farklı aydınlık ve karanlık peryotlarda geliştirlen kültürlerde, hücre sayısı, klorofil ve protein miktarında önemli değişimlerin olduğunu ortaya koymuştur. Maximum büyüme oranı 16/8 saatlik peryotta gerçekleşmiştir. Aynı zamanda protein ve klorofil miktarlarının da farklı ışık peryotlarında dikkate değer değişimler gösterdiği belirlenmiştir. Maximum protein ve klorofil miktarına (235, 53; 386, 5 µg/mL) 20/4 saatlik peryotta ulaşıldığı gözlemlendi.
Chlorella vulgaris’in gelişimi, protein miktarı ve pigment içeriği üzerinde fotoperiyodun etkisi